PENGARUH KOMPETENSI KARYAWAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MUTIARA MUKTI FARMA (BERGERAK DALAM BIDANG OBAT-OBATAN) - Indah Lestari; Lamtiur Sidabutar; Devi Arianti Sirait; Memo Sitorus (JURNAL MANAJEMEN, 2019)
Competence is something that is embedded in the employee who is a supporter in carrying out his responsibilities. Competence can also be said as skills, knowledge, basic attitudes and values reflected in the habit of thinking and acting that are developing, dynamic, continuous and can be achieved at any time. In addition to competence, work discipline is one of the tools used by managers to change the behavior of employees to comply with all company regulations. For this reason, the company needs to monitor every action and behavior carried out by employees while working. The purpose of this study was to determine the effect of competence and discipline on the performance of employees at PT. Mutiara Mukti Farma. The analysis method uses multiple linear regression analysis; the study population was 142 employees with a sample of 105 respondents. The results of the study show that competence and discipline together influence employee performance.